Differentiated Approaches to Chemotherapy of Respiratory Tuberculosis in Children Exposed to Isoniazid Resistant Tuberculosis - M. F. Gubkina; I. Yu. Рetrakova; N. V. Yukhimenko; S. S. Sterlikova; Yu. Yu. Khokhlova (Туберкулез и болезни лёгких)
The objective of the study: evaluation of the results of differentiated approaches to chemotherapy of respiratory tuberculosis in children exposed to isoniazid resistant tuberculosis.Subjects and Methods. 57 children aged 2-12 years were enrolled in the study (the median age made 8 years) all children suffered from active respiratory tuberculosis and received conservative therapy only All children were exposed to isoniazid resistant tuberculosis. Patients were divided into two groups. Group 1 received standard chemotherapy regimen 2: 5 anti-tuberculosis drugs (TB drugs) in the intensive phase and 4 TB drugs in the continuation phase (5 TB drugs/4 TB drugs) for disseminated processes (25 patients); Group 2 - 32 patients who received individualized regimens: 4 TB drugs/3 TB drugs for the limited disease (14 patients); 3 TB drugs for the whole course of chemotherapy for minor forms (18 patients). The combination of TB drugs was based on the susceptibility of the index case.Results. Treatment outcomes in all children were classified as effective treatment. The intensive phase of chemotherapy made 4.2 ± 0.3 months in Group 1 and 2.8 ± 0.2 months in Group 2, pt < 0.05. The total duration of chemotherapy in Group 1 made 9.9 ± 0.3 months, and in Group 2 was 6.8 ± 0.2 months, pt < 0.05. Conclusion. The use of individual regimens of anti-tuberculosis chemotherapy consisting of the fewer number of drugs and with a shorter duration of treatment, does not impair effectiveness of chemotherapy of respiratory tuberculosis in case of the limited disease and minor lesions in children exposed to isoniazid resistant tuberculosis.